Faktor Faktor yang Mempengaruhi Pendapatan Petani Cengkeh di Desa Rante Alang Kecamatan Larompong Kabupaten Luwu - Ramlan, Ramlan; Irmayani, Irmayani; Nurhaeda, Nurhaeda (Penerbit Goodwood, 2023)
Purpose: This study aims to determine the influence of the amount of production on the income of clove farmers in Rante Alang Village, Larompong District, Luwu Regency. Research Methodology: The research adopts a descriptive quantitative approach. The total population consists of 856 clove farmers in Rante Alang Village, with 90 individuals selected as respondents. Data were collected through structured questionnaires and analyzed using multiple linear regression. Results: The findings indicate that production costs, selling price, land area, and the amount of production each have a significant and positive effect on the income of clove farmers. Among these, the amount of production is shown to be a critical factor, confirming that increases in production volume contribute directly to higher income levels. The statistical results meet the significance threshold, thus supporting the hypothesis that these variables are influential in determining farmer income in the study area. Conclusion: This study concludes that improving production output, alongside optimizing land usage and pricing strategies, can effectively enhance the income of clove farmers. These variables play a crucial role in shaping the financial sustainability of agricultural households. Limitations: The scope of this research is limited to a single village and a sample of 90 respondents, which may not fully represent broader agricultural conditions in other regions. Contribution: The study offers empirical evidence that can inform agricultural development programs and financial planning for clove farmers, particularly in similar rural contexts.